Bayesian Network Expert System for Early Diagnosis of Heart Diseases - Mohamad Saad A.Sawa; Agus Naba; Harry Soekotjo Dachlan (Fakultas Teknik, Universitas Brawijaya, 2013)
Heart disease is a deadly disease in the world. Some countries that have a high risk of death are America, Australia and England. It is difficult for a person do a medical checkup not only because of the financial matter but also because they don't care about it. This study is to help people on early diagnose to the risk of heart disease. Expert System is used as the basis of this study which is using Bayesian Network algorithms with datasets from previous studies conducted in Europe. The objective of this research are (1) to design knowledge base, inference engine with Bayesian network for early diagnose of heart diseases, (2) to develop web-based system that help people to get early diagnose of risk heart disease. This study was conducted by the help of a heart disease specialist and internist that helps validate the dataset and the results of research through application testing detection of heart disease risk. This result is consistent with the analysis that can be used by physicians and public.Index Terms—expert system, Bayesian network, heart disease, early diagnose.